Analisis sistem pengawasan pemberian pembiayaan pada PT. Bank Sulselbar Syariah Cabang Utama Makassar - ela elliyana; Ahmed Benyahia Rabia; Rishka Sri Mulyani (Economy Deposit Journal (E-DJ), 2019)
This type of research uses associative / quantitative research which is a study that aims to find out the Supervision Analysis of Financing in PT Bank Sulselbar Syariah Main Branch of Makassar. The location of this study took place at PT. Bank Sulselbar Syariah Cab. Makassar. The data source is a list of customer collectability. Techniques for collecting data through primary data in the form of questionnaires and secondary data in the form of documents related to the research title. The data obtained is then analyzed through several stages including editing, coding, data tabulation, and interpreted into a descriptive. The results of the study obtained that the handling of problematic financing carried out by PT PT. Bank Sulselbar Syariah through collection staff by means of a combination of regular collection and margin discounts has the greatest success rate. On a regular basis collection collection staff come to customers directly, then customers are offered a margin discount provided that the customer has the criteria set by the board of directors. The average level of non-performing loans is 14.91%, which means that the non-performing level of musyarakah loans is 14.91% of the total funding provided by Sulselbar Syariah Bank. Whereas the maximum non-performing loan of musharaka financing occurred in March 2015 amounting to 40.01% which was caused by the reduced ability to pay from mudharib, in this case the Sulselbar Syariah Bank would have to make a backup which of course in turn reduced the risk of capital adequacy the level of non-performing loans of PT. Bank Sulselbar Syariah has increased from the previous quarter. This is due to an increase in credit is not smooth